2021
DOI: 10.3389/fctls.2021.669260
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Noble Metal-Free Ti@TiO2 Photocatalyst for Boosting Photothermal Hydrogen Production

Abstract: In this work, we provide new insights into the design of Ti@TiO2 photocatalyst with enhanced photothermal activity in the process of glycerol reforming. Ti@TiO2 nanoparticles have been obtained by sonohydrothermal treatment of titanium metal nanoparticles in pure water. Variation of sonohydrothermal temperature allows controlling nanocrystalline TiO2 shell on Ti0 surface. At 100 < T < 150°C formation of TiO2 NPs occurs mostly by crystallization of Ti(IV) amorphous species and oxidation of titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
5
15
0
Order By: Relevance
“…As also reported in our previous work [18], diffuse reflectance spectra for both Ti 0 and Ti@TiO 2 NPs exhibit a broad band in the UV-NIR spectral range corresponding to the interband transitions of metallic Ti 0 . The presence of TiO 2 on the surface of the metallic NPs promotes the formation of a characteristic absorption peak around 298 nm.…”
Section: Samples Mol% Ti Ti 3 O Tiosupporting
confidence: 85%
See 3 more Smart Citations
“…As also reported in our previous work [18], diffuse reflectance spectra for both Ti 0 and Ti@TiO 2 NPs exhibit a broad band in the UV-NIR spectral range corresponding to the interband transitions of metallic Ti 0 . The presence of TiO 2 on the surface of the metallic NPs promotes the formation of a characteristic absorption peak around 298 nm.…”
Section: Samples Mol% Ti Ti 3 O Tiosupporting
confidence: 85%
“…Recently, it has been reported [18] that the XPS spectrum of air passivated Ti NPs exhibits the presence of Ti 0 and lower oxidation states of titanium (TiO, Ti x O y and Ti 2 O 3 ) at the particle surface in agreement with the XRD analysis revealed the presence of titanium suboxide in Ti 0 NPs. SHT treatment causes disappearance of Ti 0 , TiO, Ti x O y and Ti 2 O 3 peaks, and the experimental XPS spectrum of Ti@TiO 2 NPs can be fitted by defect-free TiO 2 spectrum, indicating effective coating of metallic titanium core.…”
Section: Samples Mol% Ti Ti 3 O Tiosupporting
confidence: 73%
See 2 more Smart Citations
“…These include metals like Ni, Fe, and Co, and others. Various studies ( Khan et al, 2016 ; Abdullah et al, 2017 ; Chen et al, 2020b ; Baig et al, 2021 ) have shown the effects of different metal oxide supported catalysts like La 2 O 3 , ZiO 2 , Al 2 O 3 , SiO 2 , and TiO 2 involved in producing hydrogen ( Kim et al, 2011 ; El Hakim et al, 2021 ). In a study by Ibrahim et al , it was found that Fe over La 2 O 3 showed promising results for TMD at temperatures ranged between 500 and 700°C.…”
Section: Catalystsmentioning
confidence: 99%